#TITLE_ALTERNATIVE# - ROHMAN HUKAMA (NIM : 227 10 304) ; Pembimbing : Dr. rer. nat. Ir. Lilik Eko Widodo, MS., IFTITAH
The implementation of gravity method in oil and gas industries has a goal in defining the shape and distribution of hydrocarbonÃ‚Â’s masses. On the survey we had done before, the groundmass and water mass which stored inside the rock pores are also measured together, including water in unsaturated zone. Because of that, the other masses must be isolated. This process is usually called microgravity correction. The research is done in Banyuurip area. The research area is surrounded by Bengawan Solo on the north, also as the lowest point of all, a group of elongated hills which have east-west strike orientation on the south side. On the west and east side, it is confined by river which is a part of Bengawan Solo. Water mass (water content) in unsaturated zone is closely related to the degree of saturation. To be able to achieve that degree of saturation, we need to understand the hysteresis curve, which shows us the relationship between the degree of saturation and capillary pressure. Capillary pressure can be gained by simplify (linearization) the vertical distribution of capillary pressure with the water table as the benchmark. Capillary pressure on the water table will be the same as the atmospheric pressure, on the other hand, the pressure above the water table will have a negative value and usually known as tension or suction. The distribution pattern of water table follows the topographic condition of the research area. The flows start from south to north. The integration between water table measurements data and analysis result of rock/soil samples will produce the degree of saturation. Then, the degree of saturation will be used to produce the microgravity correction. The calculation of microgravity correction in unsaturated zone will yield .95 Ã‚Â– 1.40 μgal. This value is enough to increase the accuracy of microgravity correction due to water table changes around 10 Ã‚Â– 15%.